2019
DOI: 10.23887/jish-undiksha.v8i2.22375
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Promosi Berbasis Sosial Media Terhadap Penjualan Produksi Kelompok Wanita Tani (Kwt) Ayu Tangkas Di Desa Megati

Abstract: Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh promosi berbasis sosial media terhadap hasil penjualan produksi pertanian Kelompok Wanita Tani (KWT) Ayu Tangkas di Desa Megati Kabupaten Tabanan. Penelitian ini dilaksanakan di Desa Megati Kecamatan Selemadeg Barat Kabupaten Tabanan yang melibatkan KWT Ayu Tangkas yang berperan dalam mengolah hasil pertanian menjadi makanan yang siap jual. Penentuan responden ditunjuk secara purposive random sampling. Penelitian ini menggunakan pendekatan penelitian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
1
4
0
2
Order By: Relevance
“…Based on these results, it meant that social media Instagram-based promotion had a significant effect on the sales of the products of KWT Ayu Tangkas in Megati village, Tabanan regency. The similarity between current research and the one conducted by Setiawan et al (2019), is that both are discussing promotion on social media towards the increase of sales. The difference between current research and the previous research is the research object.…”
Section: Literature Reviewmentioning
confidence: 80%
See 2 more Smart Citations
“…Based on these results, it meant that social media Instagram-based promotion had a significant effect on the sales of the products of KWT Ayu Tangkas in Megati village, Tabanan regency. The similarity between current research and the one conducted by Setiawan et al (2019), is that both are discussing promotion on social media towards the increase of sales. The difference between current research and the previous research is the research object.…”
Section: Literature Reviewmentioning
confidence: 80%
“…Based on the theoretical basis and research results of Setiawan et al (2019) which analyzed "The Effect of Social Media Based Promotion towards The Sales Production of Female Farmer Group (KWT) Ayu Tangkas in Megati Village". This research showed that social media Instagram as promotion media could increase the sales production of KWT Ayu Tangkas in Megati village, Selemadeg district, East Tabanan Regency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Penentuan responden ditunjuk secara purposive random sampling. [9] 8. Penelitian yang dilakukan oleh Ade Raisha Nurgayatri dan Ama Suyanto (2016) dari Telkom University yang berjudul "Pengaruh Promosi Online Pada Media Sosial Terhadap Keputusan Pembelian Konsumen Brand Elmeira".…”
Section: Mavib Journal Vol 3 No 1 -Februari 2022unclassified
“…Dengan memaksimalkan promosi, maka produk yang diproduksi oleh anggota PKK akan dikenal secara luas oleh masyarakat. Strategi ini sejalan dengan penelitian yang dilakukan pada media sosial yang digunakan untuk mempromosikan produk sehingga dapat memberi peningkatan penjualan (Indika & Jovita, 2017;Indrawati et al, 2017;Reinhart Abedneju Sondakh et al, 2019;Setiawan et al, 2019;Untari & Fajariana, 2018).…”
Section: Matriks Swotunclassified